ANALISIS HACKING BLACK CAMPAIGN PEMILIHAN PRESIDEN 2014 di FACEBOOK - Lilik Endrawati (Metafora: Education, Social Sciences and Humanities Journal, 2020)
The study is to apply the concept of power/ knowledge Michel Foucault to examine black campaign presidential election 2014.Using perspective the Foucault these phenomena can be understood not merely causation black campaign. However, using the power and knowledge could be used to dissect the Foucault knowledge built by investors who wanted black campaign. Successful teams and even the supporters of the two camps, which are strongholds of Former stronghold Prabowo-Hatta and Jokowi-Jk battlefield mutual borrowing terms Foucault œdiscourse to win the meaning of reality that is constructed. It is therefore interesting to research this further investigated. This study uses research methods online (Online Research Method [ORMs]) analysis approach to hacking developed by M. Jacky. Analysis of hacking (hacking analysis) is the new pendekataan in the online research that is used to understand social reality of virtual internet users (Netter). By using the analytical approach to hacking can dissect the construction or the discourse of discursive and non-konstruksif of virtual reality black campaign. Engineering data collection done by identifying a non-discursive discourse, discursive, as well as the jargon file.By using the analytical approach to hacking can dissect the construction or the discourse of discursive and non-konstruksif of virtual reality black campaign. Engineering data collection done by identifying a non-discursive discourse,discursive, as well as the jargon file.